THE EFFECT OF BOARD DIVERSITY ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Wahyu Widarjo; Vidhe Kusuma Perdana; Eko Arief Sudaryono (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to provide evidence of the effect of board diversity on the disclosure of Corporate Social Responsibility (CSR) in mining sector companies listed on the Indonesia Stock Exchange from 2017 to 2020. The sample used was 156 observations taken by purposive sampling method. This study proves that there is a positive and significant effect of the diversity of the board education level on CSR disclosure. However, the results of this study do not provide evidence of a significant effect of gender diversity, nationality, and board educational background on CSR disclosure.